2016
DOI: 10.1038/leu.2016.231
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic landscape and impact in blast phase of chronic myeloid leukemia in the era of tyrosine kinase inhibitor therapy

Abstract: The landscape of additional chromosomal alterations (ACAs) and their impact in chronic myeloid leukemia, blast phase (CML-BP) treated with tyrosine kinase inhibitors (TKIs) have not been well studied. Here, we investigated a cohort of 354 CML-BP patients treated with TKIs. We identified +8, an extra Philadelphia chromosome (Ph), 3q26.2 rearrangement, -7 and isochromosome 17q (i(17q)) as the major-route changes with a frequency of over 10%. In addition, +21 and +19 had a frequency of over 5%. These ACAs demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…Epigenetic silencing of negative regulators of the Wnt signaling cascade is also frequently observed in leukemias, including CML (80). Chromosomal aberations (81), alterations in the bone marrow microenvironment (82), as well as other mechanisms, may play significant roles in LSC resistance (for a recent review on CML LSC resistance please see T. Holyoake and D. Vetrie (83) ). β-Catenin signaling has also been reported to be activated during the development of MLL (mixed-lineage leukemia) leukemic stem cells(84).…”
Section: Wnt Signaling In CMLmentioning
confidence: 99%
“…Epigenetic silencing of negative regulators of the Wnt signaling cascade is also frequently observed in leukemias, including CML (80). Chromosomal aberations (81), alterations in the bone marrow microenvironment (82), as well as other mechanisms, may play significant roles in LSC resistance (for a recent review on CML LSC resistance please see T. Holyoake and D. Vetrie (83) ). β-Catenin signaling has also been reported to be activated during the development of MLL (mixed-lineage leukemia) leukemic stem cells(84).…”
Section: Wnt Signaling In CMLmentioning
confidence: 99%
“…This phenomenon coincided with the current study. Moreover, one study reported that the emergence of the 3q26.2 rearrangement had a high frequency of correlation with BCR‐ABL1 mutations . However, other studies showed that ACAs and KD mutations were randomly combined in CML patients, representing different resistance mechanisms .…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of tyrosine kinase inhibitors (TKIs) has greatly improved the management and prognosis of CML patients, research on CML has never stopped. Current studies have found that the incidence of additional chromosomal abnormalities (ACAs) is approximately 5% in the chronic phase (CP) of CML patients, 30% in the accelerated phase (AP) and 80% in the blast phase (BP) . Hence, ACAs are considered an intrinsic factor in the progression of CML patients with a negative impact on survival and prognosis .…”
Section: Introductionmentioning
confidence: 99%
“…The results were reported with the 2016 International System for Human Cytogenetics Nomenclature as described previously . For patients with CML for whom BM biopsy was essential or helpful, the karyotype was stratified into groups with favorable, neutral, or poor cytogenetic risk according to findings reported previously …”
Section: Methodsmentioning
confidence: 99%
“…12 For patients with CML for whom BM biopsy was essential or helpful, the karyotype was stratified into groups with favorable, neutral, or poor cytogenetic risk according to findings reported previously. 2,13,14 BCR-ABL1 transcripts and cytogenetic studies were determined at diagnosis and every 3 months for a response assessment. BCR-ABL1 was detected by quantitative reverse transcriptase-polymerase chain reaction methods with RNA extracted from BM or PB samples as described elsewhere.…”
Section: Molecular and Cytogenetic Studiesmentioning
confidence: 99%